PENGARUH EDUKASI TERSTRUKTUR TERHADAP PENCEGAHAN KOMPLIKASI HIPERTENSI DI WILAYAH KERJA PUSKESMAS TILANGO - Abdul Wahab Pakaya; Nurliah Nurliah; Rian Kodai (Zaitun (Jurnal Ilmu Kesehatan), 2019)
Hypertension patients have an increased. Structured education can be done to prevent complications. The research aimed was to determine structure education effect on prevention of hypertension complications in Tilango Community Health Center. This research used a pre-experimental design with a pre-post test design and two groups (to-group pre-post test control group design). The sample in this research amounted to 40 respondents. The results based on statistical tests Paired Sample T Test obtained P value = 0.000 (<0.05) in case group. This shows that there is prevention differences of hypertension complications before and after the intervention, the control group obtained a value of P = 0.050, there is no prevention differences of hypertension complications before and after without intervention. There was structured education effect on prevention of hypertension complications in Tilango Community Health Center.